Use of nonsteroidal anti-inflammatory drugs in diabetic retinopathy - Malukiewicz, Grażyna; Stafiej, Joanna; Lesiewska, Hanna; Sikorski, Bartosz (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Introduction : Diabetic macular edema, a manifestation of diabetic retinopathy, occurs more frequently in type 2 diabetes mellitus. There is evidence that inflammation plays a prominent role in the pathogenesis. A number of pro-inflammatory cytokines are consistently elevated in the vitreous of patients with advanced stages of diabetic retinopathy. Nonsteroidal anti-inflammatory drugs inhibit the catalytic activity of the cyclooxygenase isoenzymes COX-1 and COX-2, the key enzymes in inflammatory processes. Purpose : To present current knowledge of benefits and limitations of using nonsteroidal anti-inflammatory drugs in diabetic retinopathy. Conclusions : Nonsteroidal anti-inflammatory drugs may be considered as an adjuvant treatment in diabetic retinopathy especially in patients with diabetic macular edema.